Artificial Diels–Alderase based on the transmembrane protein FhuA - Osseili, Hassan; Sauer, Daniel F.; Beckerle, Klaus; Arlt, Marcus; Himiyama, Tomoki; Polen, Tino; Onoda, Akira; Schwaneberg, Ulrich; Hayashi, Takashi; Okuda, Jun (Beilstein Journal of Organic Chemistry, 2016)
Copper(I) and copper(II) complexes were covalently linked to an engineered variant of the transmembrane protein Ferric hydroxamate uptake protein component A (FhuA ΔCVFtev). Copper(I) was incorporated using an N-heterocyclic carbene (NHC) ligand equipped with a maleimide group on the side arm at the imidazole nitrogen. Copper(II) was attached by coordination to a terpyridyl ligand. The spacer length was varied in the back of the ligand framework. These biohybrid catalysts were shown to be active in the Diels–Alder reaction of a chalcone derivative with cyclopentadiene to preferentially give the endo product.
Keywords: artificial Diels-Alderase; biohybrid catalysis; copper enyzme; membrane protein

(untitled) - Lu, Y. (Angew. Chem., Int. Ed., 2006)

(untitled) - Steinreiber, J.; Ward, T. R. (Coord. Chem. Rev., 2008)

(untitled) - Reetz, M. T. (Chem. Rec., 2012)

(untitled) - Lewis, J. C. (ACS Catal., 2013)

(untitled) - Matsuo, T.; Hirota, S. (Bioorg. Med. Chem., 2014)

(untitled) - Hayashi, T.; Sano, Y.; Onoda, A. (Isr. J. Chem., 2015)

(untitled) - Heinisch, T.; Ward, T. R. (Eur. J. Inorg. Chem., 2015)

(untitled) - Lu, Y.; Yeung, N.; Sieracki, N.; Marshall, N. M. (Nature, 2009)

(untitled) - Yu, F.; Cangelosi, V. M.; Zastrow, M. L.; Tegoni, M.; Plegaria, J. S.; Tebo, A. G.; Mocny, C. S.; Ruckthong, L.; Qayyum, H.; Pecoraro, V. L. (Chem. Rev., 2014)

(untitled) - Letondor, C.; Pordea, A.; Humbert, N.; Ivanova, A.; Mazurek, S.; Novic, M.; Ward, T. R. (J. Am. Chem. Soc., 2006)

(untitled) - Zimbron, J. M.; Heinisch, T.; Schmid, M.; Hamels, D.; Nogueira, E. S.; Schirmer, T.; Ward, T. R. (J. Am. Chem. Soc., 2013)

(untitled) - Chatterjee, A.; Mallin, H.; Klehr, J.; Vallapurackal, J.; Finke, A. D.; Vera, L.; Marsh, M.; Ward, T. R. (Chem. Sci., 2016)

(untitled) - Lo, C.; Ringenberg, M. R.; Gnandt, D.; Wilson, Y.; Ward, T. R. (Chem. Commun., 2011)

(untitled) - Mayer, C.; Gillingham, D. G.; Ward, T. R.; Hilvert, D. (Chem. Commun., 2011)

(untitled) - Matsuo, T.; Imai, C.; Yoshida, T.; Saito, T.; Hayashi, T.; Hirota, S. (Chem. Commun., 2012)

(untitled) - Basauri-Molina, M.; Verhoeven, D. G. A.; van Schaik, A. J.; Kleijn, H.; Klein Gebbink, R. J. M. (Chem. – Eur. J., 2015)

(untitled) - Philippart, F.; Arlt, M.; Gotzen, S.; Tenne, S.-J.; Bocola, M.; Chen, H.-H.; Zhu, L.; Schwaneberg, U.; Okuda, J. (Chem. – Eur. J., 2013)

(untitled) - Sauer, D. F.; Bocola, M.; Broglia, C.; Arlt, M.; Zhu, L.-L.; Brocker, M.; Schwaneberg, U.; Okuda, J. (Chem. – Asian J., 2015)

(untitled) - Sauer, D. F.; Himiyama, T.; Tachikawa, K.; Fukumoto, K.; Onoda, A.; Mizohata, E.; Inoue, T.; Bocola, M.; Schwaneberg, U.; Hayashi, T.; Okuda, J. (ACS Catal., 2015)

(untitled) - Zhao, J.; Kajetanowicz, A.; Ward, T. R. (Org. Biomol. Chem., 2015)

(untitled) - Zhang, C.; Srivastava, P.; Ellis-Guardiola, K.; Lewis, J. C. (Tetrahedron, 2014)

(untitled) - Reetz, M. T.; Jiao, N. (Angew. Chem., Int. Ed., 2006)

(untitled) - Podtetenieff, J.; Taglieber, A.; Bill, E.; Reijerse, E. J.; Reetz, M. T. (Angew. Chem., Int. Ed., 2010)

(untitled) - Deuss, P. J.; Popa, G.; Slawin, A. M. Z.; Laan, W.; Kamer, P. C. J. (ChemCatChem, 2013)

(untitled) - Bos, J.; Fusetti, F.; Driessen, A. J. M.; Roelfes, G. (Angew. Chem., Int. Ed., 2012)

(untitled) - Himiyama, T.; Sauer, D. F.; Onoda, A.; Spaniol, T. P.; Okuda, J.; Hayashi, T. (J. Inorg. Biochem., 2016)

(untitled) - Ghattas, W.; Cotchico-Alonso, L.; Maréchal, J.-D.; Urvoas, A.; Rousseau, M.; Mahy, J.-P.; Ricoux, R. (ChemBioChem, 2016)

(untitled) - Nicolaou, K. C.; Snyder, S. A.; Montagnon, T.; Vassilikogiannakis, G. (Angew. Chem., Int. Ed., 2002)

(untitled) - Reymond, S.; Cossy, J. (Chem. Rev., 2008)

(untitled) - Kagan, H. B.; Riant, O. (Chem. Rev., 1992)

(untitled) - Tenne, S.-J.; Schwaneberg, U. (Int. J. Mol. Sci., 2012)

(untitled) - Otto, S.; Engberts, J. B. F. N.; Kwak, J. C. T. (J. Am. Chem. Soc., 1998)

(untitled) - Fulmer, G. R.; Miller, A. J. M.; Sherden, N. H.; Gottlieb, H. E.; Nudelman, A.; Stoltz, B. M.; Bercaw, J. E.; Goldberg, K. I. (Organometallics, 2010)

(untitled) - Occhipinti, G.; Jensen, V. R.; Törnroos, K. W.; Frøystein, N. Å.; Bjørsvik, H.-R. (Tetrahedron, 2009)

(untitled) - Perera, A. S.; Subbaiyan, N. K.; Kalita, M.; Wendel, S. O.; Samarakoon, T. N.; D’Souza, F.; Bossmann, S. H. (J. Am. Chem. Soc., 2013)

(untitled) - Constable, E. C.; Ward, M. D. (Dalton Trans., 1990)

(untitled) - de Figueiredo, R. M.; Oczipka, P.; Fröhlich, R.; Christmann, M. (Synthesis, 2008)